2021
DOI: 10.3389/fonc.2020.603216
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Complexity and Outcome During the Implementation Phase of a Robotic Colorectal Surgery Program—A Retrospective Cohort Study

Abstract: BackgroundRobotic surgery holds particular promise for complex oncologic colorectal resections, as it can overcome many limitations of the laparoscopic approach. However, similar to the situation in laparoscopic surgery, appropriate case selection (simple vs. complex) with respect to the actual robotic expertise of the team may be a critical determinant of outcome. The present study aimed to analyze the clinical outcome after robotic colorectal surgery over time based on the complexity of the surgical procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…As the learning curve and efficiency of robotic colorectal surgery improves with increasing usage and technological advances, it is probable that operative time will also decrease. In fact, Müller et al 41 . found that in robotic colorectal surgery patients, operative time and major complications significantly decreased between two time periods of consecutive patients.…”
Section: Discussionmentioning
confidence: 99%
“…As the learning curve and efficiency of robotic colorectal surgery improves with increasing usage and technological advances, it is probable that operative time will also decrease. In fact, Müller et al 41 . found that in robotic colorectal surgery patients, operative time and major complications significantly decreased between two time periods of consecutive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bencini et al 13 suggested beginning robotic right hemicolectomy (RRH) to reduce the learning curve for more challenging procedures, such as robotic rectal resection (RRR). However, the development of robot systems in simple surgery regarding the standard laparoscopic approach is less evident compared to complex cases 14 . Surgeon A performed standard surgery in the initial step, and surgeon B chose complex surgery in the initial step.…”
Section: Discussionmentioning
confidence: 99%
“…Muller shows that the Miskovic complexity score correlates with the rate of major complications in robotic colorectal surgery, especially if the surgeon is not proficient in robotic surgery [ 33 ]. Therefore, the learning curve should be used and taken as an important factor, when selecting complex cases to be perfomed via robotic approach [ 33 ]. This will lead to a significant reduction in major complications over time [ 33 ].…”
Section: Reviewmentioning
confidence: 99%